If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 7)(x + -2) = (x + 1)(x + 1) Reorder the terms: (7 + x)(x + -2) = (x + 1)(x + 1) Reorder the terms: (7 + x)(-2 + x) = (x + 1)(x + 1) Multiply (7 + x) * (-2 + x) (7(-2 + x) + x(-2 + x)) = (x + 1)(x + 1) ((-2 * 7 + x * 7) + x(-2 + x)) = (x + 1)(x + 1) ((-14 + 7x) + x(-2 + x)) = (x + 1)(x + 1) (-14 + 7x + (-2 * x + x * x)) = (x + 1)(x + 1) (-14 + 7x + (-2x + x2)) = (x + 1)(x + 1) Combine like terms: 7x + -2x = 5x (-14 + 5x + x2) = (x + 1)(x + 1) Reorder the terms: -14 + 5x + x2 = (1 + x)(x + 1) Reorder the terms: -14 + 5x + x2 = (1 + x)(1 + x) Multiply (1 + x) * (1 + x) -14 + 5x + x2 = (1(1 + x) + x(1 + x)) -14 + 5x + x2 = ((1 * 1 + x * 1) + x(1 + x)) -14 + 5x + x2 = ((1 + 1x) + x(1 + x)) -14 + 5x + x2 = (1 + 1x + (1 * x + x * x)) -14 + 5x + x2 = (1 + 1x + (1x + x2)) Combine like terms: 1x + 1x = 2x -14 + 5x + x2 = (1 + 2x + x2) Add '-1x2' to each side of the equation. -14 + 5x + x2 + -1x2 = 1 + 2x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -14 + 5x + 0 = 1 + 2x + x2 + -1x2 -14 + 5x = 1 + 2x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -14 + 5x = 1 + 2x + 0 -14 + 5x = 1 + 2x Solving -14 + 5x = 1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -14 + 5x + -2x = 1 + 2x + -2x Combine like terms: 5x + -2x = 3x -14 + 3x = 1 + 2x + -2x Combine like terms: 2x + -2x = 0 -14 + 3x = 1 + 0 -14 + 3x = 1 Add '14' to each side of the equation. -14 + 14 + 3x = 1 + 14 Combine like terms: -14 + 14 = 0 0 + 3x = 1 + 14 3x = 1 + 14 Combine like terms: 1 + 14 = 15 3x = 15 Divide each side by '3'. x = 5 Simplifying x = 5
| 1.4(x+1.2)=7.8 | | -24/5=31/2h | | (x+7)(x+2)=(x+1)(x+1) | | m=z+bx | | 12x+8y+7x=z | | 2(3x-4)+6(x-5)=-3(4-5x)+5x-16 | | 4y-1x+2y=z | | [8+(-4)]-5= | | -8/12-21/12 | | 12+[-5+(-4)]= | | (7/x)-(1/7)=(2/x) | | 3(3x-2)=15 | | 2(3x-5)+6(x-3)=-3(3-5x)+5x-1 | | 2-4(x+3)=4-2(3x+5) | | 2.5=2/s | | -2(-3)-5y=4 | | -2y-42=3(y+1) | | -2/3(6*3-45)-2(3) | | 9x+2x=0x | | 21-u=17 | | 3x^2-4y=7 | | 2/5*15-1=5 | | (6a+1)(5a+2)= | | 5x-(4x+5)=3x-33 | | 441800*8*5/12 | | 992400*8*5/12 | | -16/n=32 | | 7X-3=4+6X | | 3a^2(a^2b^2+b)= | | (8/4)-(15/4) | | 8/4-15/4 | | 3(2x+4)-5= |